PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN - Ramadhani, Zakky; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to test the influence of corporate social responsibility (CSR) to firm value. Variable of CSR consist/s of seven areas of disclosure: environment (LKI), energy (EGI), the health and safety of labors (KKT), labor miscellaneous (LTK), product (PRO), public involvement (KMA) and public, firm value in this research which is proxy by price book to value (PBV). The samples are mining sector companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2015 periods and these companies have been selected by using purposive sampling, and 116 observation data of the financial statements of 29 companies have been selected as samples.The result of the research which has been analyzed by using multiple regressions analysis shows KKT, PRO and KMA. give positive influence to the firm value, LKI, EGI, and LTK and UMM do not give any significant influence to the firm value. TheAdjusted R-square is 0.33 or 33% variation of the PBV has been able to explained by the variables of LTI, EGI, KKT, LTK, PRO, KMA and UMM, whereas the remaining 67% has been explained by other variables.Keywords: environment (LKI), Corporate Social Responsibility (CSR), firm value (PBV)